ECOLOGICALLY UNEQUAL EXCHANGE, AND FOREST LOSS: HOW AFRICA'S DEMAND FOR CPO IMPACTS THE NATURAL ENVIRONMENT IN INDONESIA? - Nugraha, Fadel; Tarit, Pauline Chepkwisich; Sebalo, Tumelo; Anggrayni, Devi; Susilowati, Indah (Jurnal Ekonomi dan Bisnis Airlangga, 2025)
Introduction: This study examines the environmental consequences of increased Indonesian crude palm oil (CPO) exports to African markets, emphasizing deforestation impacts. Methods: Using annual time-series data from 1980 to 2023, an Autoregressive Distributed Lag (ARDL) econometric model is employed to capture both short-term dynamics and long-term equilibrium relationships. Results: The findings robustly confirm the Ecologically Unequal Exchange (EUE) hypothesis, revealing significant negative impacts of Indonesian palm oil exports on domestic forest cover. Specifically, increased palm oil exports, agricultural land expansion, GDP growth, migration patterns, and demographic pressures from urban and rural populations collectively exacerbate deforestation rates. Empirical results also confirm a stable long-term cointegration among these variables, highlighting enduring environmental risks associated with export-driven agricultural strategies. Conclusion and suggestion: Policymakers must integrate sustainability into trade policies, enhance international cooperation for responsible agricultural practices, and strengthen regulatory frameworks to mitigate environmental damage effectively.